การคำนวณออกแบบอย่างเหมาะสมสำหรับคานคอนกรีตต่อเนื่องอัดแรงบางส่วน - ธัญญาภรณ์ วั่นเลี่ยง (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
To present an optimal design method for partially prestressed concrete continuous beams. The design is based on partial prestressing ratio (PPR) concept proposed by Naaman and Siriaksorn. Following the ACI building code (ACI 318M-02) the structures must satisfy the requirements at prestress transfer, at service, at ultimate and so on. The optimal design appoints the total cost of concrete, prestressing tendons, nonprestressed reinforcement, stirrups, and formwork as the objective function. The solution is sought for the partially prestressed concrete continuous beam with sufficient strengths and optimal cost. Results from case studies indicated that the optimal design reduce the construction cost by approximately 12% when comparing with the design of conventional prestressed concrete beam. Moreover, it is found that varying the depth of the beam to a more appropriate value can yield some further cost reduction.